Nursing research progress of peristomal irritant dermatitis in patients with enterostomy (肠造口患者造口周围粪水刺激性皮炎的护理研究进展) - ZHANG Baoli (张宝丽); WANG Yan (王艳) (中西医结合护理)
Health-related quality of life (HRQoL) is often markedly impaired in patients with peristomal irritant dermatitis. This article reviewed the etiology, nursing evaluation and intervention measures of irritant contact dermatitis in patients with enterostomy, to provide targeted and scientific basis for clinical practice of prevention and treatment of irritant dermatitis after enterostomy, reduce patients' pain, and improve patients' compliance and self-care ability. (造口周围粪水刺激性皮炎严重影响肠造口患者生活质量。本文通过对肠造口患者造口周围粪水刺激性皮炎的病因、护理评估、干预措施进行综述, 旨在为临床护理人员防治造口周围粪水刺激性皮炎提供有针对性的科学依据。)